FACTORS INFLUENCING PREVALENCE OF MALARIA AMONG CHILDREN UNDER FIVE YEARS ATTENDING PEDIATRICWARD AT HOIMA REGIONAL REFERRAL HOSPITAL, HOIMA DISTRICT. A CROSS-SECTIONAL STUDY. - Kamuhaise Gillian (Student's Journal of Health Research, 2023)
Introduction: The objectives were to determine the prevalence, Socio-demographic, and environmental factors influencing the prevalence of malaria among children under five years attending the pediatric ward at Hoima Regional Referral Hospital, Hoima district. Methodology: The study was a descriptive cross-sectional study of 100 respondents, selected by simple random sampling technique, data was selected using self-administered questionnaires and the researcher assisted in interpreting for the illiterates. Findings: The prevalence of malaria among children under five years was (92/100) 92%. Most 92(92%) had ever suffered from malaria, half 50(50%) of the respondents reported the death of children under five years due to malaria, majority 90(90%) reported that malaria was commonest in a rural setting, 90(90%) slept under insecticide-treated nets, all 100(100%) obtained their insecticide-treated nets freely from health centers, majority 80(80%) controlled mosquito population in their area by slashing, all 100(100%) reported that mother's education influenced malaria prevalence, all 100(100%) reported that malaria was commonest in the wet season, most 99(99%) reported more malaria prevalence in areas(warm) near the equator, most 40(40%) reported more mosquito bites in the grass thatched lastly more than half 76(76%) reported that malaria was more in low land. Conclusion: The study found that the prevalence of malaria is very high among children under five years attending pediatric wards in HRRH. This was influenced by being in a rural setting, low level of mother's education, being peasants, wet season, being near the equator, humidity, and sleeping in grass-thatched houses. Poor control of the mosquito population, and not sleeping in well-ventilated houses with mosquito traps were the other factors Recommendations: The government in conjunction with the administration and health workers of HRRH should carry out regular and comprehensive health education programs and campaigns regarding malaria. Supporting and providing easy access to health centers and prompt management of those affected.